Análisis de parámetros cinemáticos y de activación eléctrica muscular del salto vertical en hombres y mujeres utilizando OpenPose y registros EMG (2023)
In this project the results of an analysis of kinematic parameters and electrical activation of the vertical jump of men and women are evidenced, presenting because of studies through OpenPose and EMG records, to compare and establish whether there are significant differences between the data obtained. The proposal lies, on the one hand, the acquisition of kinematic data, which is done with markerless technology type OpenPose. On the other hand, that simultaneously and synchronized muscle activation data are recorded, through the electromyography registry (EMG).